Is single visit endodontic treatment possible for type 1 diabetic patient?: A case report - Lolong, Jade M.; Hikmah, Noor; Natsir, Nurhayaty; Nugroho, Juni J.; Trilaksana, Aries C.; Dwiandhany, Wahyuni S. (Journal of Case Reports in Dental Medicine, 2023)
Objective: To describe single visit endodontic treatment in patient with type 1 diabetes.Methods: Patient has history of type 1 diabetes. Intraoral examination showed caries on occlusal #36, positive vitality, negative on percussion and palpation. Radiograph showed normal periapical tissue. The diagnosis of #36 was asymptomatic irreversible pulpitis.Results: Preparation begins with establishing glide path using ProGlider, cleaning and shaping with ProTaper Gold. The canals were irrigated using 5,25% NaOCl, 17% EDTA, and aquadest then activated by ultrasonic. The obturation was done using single cone technique with resin-based sealer followed by post endodontic composite restoration.Conclusion: Single visit endodontic has minimum chair time without compromising the quality of treatment specifically for type 1 diabetic patient while still prioritizing the principle of proper case selection and following standard endodontic protocols.